Exploração da organocatálise na síntese de intermediários de compostos com potencial biológico - Pontes, João Guilherme de Moraes (2013)
In recent decades the use of small molecules acting as catalyst has emerged as a powerful tool to the synthesis of new molecules which have potential biological application. This new model of catalysis provides others advantages to conventional methods, for example, easy handling and catalyst storage, since in most cases the catalyst are stable compounds to air and moisture; cost, energy and chemical waste reduction. The Organocatalysts can interact with substrates by different modes of activation, one of these, through non-covalent interactions such as hydrogen bond which has been extensively studied employing the following catalysts: ureas, thioureas, guanidines, squaramides and silanediols. Herein we is reported the 1,1-diamine-nitroethylene scaffold as a new class of organocatalyst to be explored in Michael addition reactions, which activate the acceptor in the transition state through hydrogen bonds donation. The relative easy synthesis and handling of these compounds, due no need of inert or anhydrous conditions together with the low cost of raw materials enables this new class as a potential tool to be considered and worked in the area of organocatalysis. The application of theses catalyst in the Michael additions has led to good yields and diastereoisomeric ratio. In this study we characterized the bifunctional organocatalyst using 1D and 2D NMR techniques. The application of this catalyst in Michael reactions with different classes of nucleophiles and nitroolefins, led to the desired products in good reaction yields and d.r.